Association between walking energy utilisation and longitudinal cognitive performance in older adults. (19th December 2022) - Kuo, Pei-Lun; An, Yang; Gross, Alden L; Tian, Qu; Zipunnikov, Vadim; Spira, Adam P; Wanigatunga, Amal A; Simonsick, Eleanor M; Ferrucci, Luigi; Resnick, Susan M; Schrack, Jennifer A
Abstract: Background: Human motor function is optimised for energetic efficiency, however, age-related neurodegenerative changes affects neuromotor control of walking. Energy utilisation has been associated with motor performance, but its association with cognitive performance is unknown. Methods: The study population included 979 Baltimore Longitudinal Study of Aging participants aged 50 years (52% female, mean age: 70± 10.2 years) with a median follow-up time of 4.7 years. Energy utilisation for walking was operationalised as a ratio of the energy cost of slow walking to peak walking energy expenditure during standardised tasks ('cost-ratio'). Cognitive functioning was measured using the Trail Making Tests, California Verbal Learning Test, Wechsler Adult Intelligence Scale (WAIS), letter and category fluency and card rotation tests. Linear mixed models adjusted for demographics, education and co-morbidities assessed the association between baseline cost-ratio and cognitive functioning, cross-sectionally and longitudinally. To investigate the relationship among those with less efficient energy utilisation, subgroup analyses were performed. Results: In fully adjusted models, a higher cost-ratio was cross-sectionally associated with poorer performance on all cognitive tests except WAIS ( P < 0.05 for all). Among those with compromised energy utilisation, the baseline cost-ratio was also associated with a faster decline in memory (long-delay free recall: β = −0.4, 95% confidence interval [CI] = [−0.8, −0.02]; immediate word recall: β = −1.3, 95% CI = [−2.7, 0.1]). Conclusions: These findings suggest cross-sectional and longitudinal links between energy utilisation and cognitive performance, highlighting an intriguing link between brain function and the energy needed for ambulation. Future research should examine this association earlier in the life course to gauge the potential for interventive mechanisms.